PURWARUPA SISTEM PENGENDALIAN DAN PEMANTAUAN SUHU DAN KELEMBABAN RUANGAN BERBASIS WEB DENGAN ATMEGA16 - , IFTITAHATUL HANIFAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A prototype of controlling and monitoring system of the roomâs temperature and humidity based on web using ATMega16 has been made. This prototype is designed to facilitate the users in monitoring and controlling the roomâs temperature and humidity. The system consists of temperature and humidity sensor SHT11, a fan controller, a relay circuit, a microcontroller system and a software system. The controlling and the outcome of the roomâs temperature and humidity measurements will be processed and displayed on web on the local host. The system of monitoring and controlling the roomâs temperature and humidity is designed using the sensor of temperature and humidity SHT11, microcontroller ATMega16, serial of communication devices using cable DKU5 and software program. The software program uses Visual Basic 6.0 and MySQL 5.1 program as the data basis storage, also Visual Studio 2008 as the web program. The controlling and monitoring system can be implemented using microcontroller ATMega16 and web on the local host. Sensor SHT11 which is positioned in one side of the room is used to detect the changes occurs on the temperature and humidity of the room. The data from the sensor will be the input of the microcontroller ports which then will be controlled and monitored. The temperature control will activate or deactivate the actuator depends on the condition filled so that the temperature and humidity of the room can be watched over. As for the actuator control in hairdryer and fan, it uses set point control which can be selected. On the other hand, the set point control in the mist maker has been installed on the system so it is unchangeable.